Lifestyle-Integrated Functional Exercise (LiFE) Program to Prevent Falls [Participant's Manual] - Clemson, Lindy (Sydney University Press, 2014)
The Lifestyle-integrated Functional Exercise (LiFE) program is a way of reducing the risk of falls by integrating balance and strength activities into regular daily tasks. Unloading the dishwasher becomes an opportunity to improve strength. Brushing your teeth becomes an opportunity to improve balance. In the LiFE program, every daily task becomes an opportunity to improve balance and strength. This is a different approach to a traditional program where you would be required to complete a series of exercises a certain number of times a day for a set number of days each week. The participant's manual outlines the principles of the LiFE program and provides detailed descriptions of the strength and balance activities in the program. It shows how the activities can be incorporated into an everyday routine and includes several stories of successful participants in the program. The participant's manual should also be read by therapists and trainers so that they are familiar with the LiFE program in its entirety and can teach it effectively to others. For hospitals, health services, and other groups that offer LiFE Training to the community, a 50 per cent discount is available for the participant's manual if 10 or more copies are orders. Please contact us for further details. A trainer's manual is also available.